Physical activity referral scheme components: a study protocol for systematic review and meta-regression - Mino, Eriselda; Geidl, Wolfgang; Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2021)
Introduction In its attempt to establish effective physical activity promotion methods, research on physical activity referral schemes (PARS) is attracting significant attention. Sometimes known as physical activity on prescription schemes, PARS involve a well-defined procedure whereby a primary healthcare professional introduces a participant to the topic of physical activity and employs prescription or referral forms to connect the participant to physical activity opportunities, such as local fitness offers. The planned systematic review will focus on these referral routes and scheme components and how they are integrated into various PARS models worldwide. We seek to identify the evidence-based core components that play the most important roles in the effectiveness of PARS. Methods and analysis The development and reporting of the protocol follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. We plan to conduct a systematic main literature search on PubMed, Scopus, Web of Science, CINAHL, HTA, SpringerLink and other databases. We will include studies that report outcomes on physical activity, PARS uptake and adherence rates or descriptive information about PARS models. We intend for all review stages, citation screening, data extraction and risk of bias assessment to be conducted by at least two independent reviewers. As a broad spectrum of study designs, including randomised and non-randomised studies of interventions and mixed methods, will be eligible, we will use three separate tools to assess the risk of bias in individual studies. The data will be primarily synthesised narratively, following Intervention Component Analysis. If the data allow, we will perform a random-effects meta-analysis and meta-regression to investigate the impact of specific PARS components on effect sizes. Ethics and dissemination This systematic review does not require formal ethics approval. The results will be submitted to a peer-reviewed journal and international conferences to reach the scientific community. PROSPERO registration number CRD42021233229.
Keywords: physical activity referral scheme; physical activity prescription; exercise referral scheme